EFFICIENCY OF VERMIFILTRATION TECHNOLOGY (VFT) IN GREY WASTEWATER BIOREMEDIATION WITH RESPECT TO CHANGE IN SOIL BEDDING MATERIAL PROPERTIES - ALIVA PATNAIK; MOUSUMI BAGHA (The Bioscan, 2024)
The present study was carried out to check the efficiency of vermifiltration technology (VFT) in grey water treatment collected from the nearby hostel of Sambalpur University and its effect on the bedding material properties of the vermibed. The study was carried out for 30 days analysing the physico-chemical properties of grey water and bedding material before and after the experiment. The result showed a significant reduction in pH, EC, TDS, TSS, BOD and COD of waste water by 16.88 %, 72.22%, 91.41%, 77.50%, 89.55%, and 76.13% respectively by the 30th day of the experiment concerning duration and retention time of the wastewater in TVB. The filtered effluent was clear and odour free as compared to sample water. The bedding material properties show significant increase in pH by 8.22%, EC by 26.05%, available phosphorous by 58.30% and potash content by 60.33% by the 30th day of study whereas significant decrease in OC content by 18.95% in TVB. Additionally, the process was odour free and sludge free.